Children with severe burn injury display no sex differences in exercise capacity at hospital discharge or adaptation after exercise rehabilitation training - Rivas, Eric (Burns, 2018)
BACKGROUND AND OBJECTIVE: Females have a 50% increased risk of death from burn injury compared to males. However, whether exercise capacity and exercise induced training adaptations differ between burned boys and girls is unknown. This project tested the hypothesis that girls with burn injury would have lower exercise capacity and different exercise induced training adaptations. METHODS: Twenty-five girls were matched to 26 boys (mean, 95%CI; years 13[12,14], cm 151[143,161], kg 54[45,63]; each P>0.05) for burn injury (% total body surface area burn, 54[45.62]; P=0.82). Lean body mass (LBM), strength (peak torque) and cardiorespiratory fitness (peak VO(2)) were normalized to kg LBM and compared as a percentage of age-sex matched non-burned children (n=26 boys, years 13[12,14]; n=25 girls, years 13[12,14]) at discharge (DC) and after aerobic and resistance rehabilitation exercise training (RET). RESULTS: Using a 2-way factorial ANOVA (group × time), we found both groups had similar 11% change in LBM (87.3% of non-burned values [82.2,92.3]) and after the RET (92.8% [87.2,98.3]; Main effect, time P<0.0001). Peak torque increased similarly by 16% in both groups (% of age-sex matched non-burned DC, 55.9[51.3,60.5]; after RET, 77.5[72.1,82.9]; Main effect, time P<0.0001). Likewise, peak VO(2) increased in both groups by 15% (% of age-sex matched non-burned DC, 56.8[52.4,61.2] to RET, 72.2[67.6,76.8]; Main effect, time; P<0.0001). Burned children exercise at greater percentage of their peak VO(2) and peak HR compared to non-burned children (Interaction, group x time, P<0.0001). CONCLUSION: The burn injury does not have sex-dependent effects on LBM or exercise capacity in severely burn injured children. Differences in relative peak VO2 and peak HR suggest the need for burn specific exercise programs for improving the efficacy of a rehabilitation.